Utilization of Coffee Grounds as an Adsorbent in Reducing the Levels of Naphthol Dyes of Weaving Industry Wastewater - Adlina Fitry; Neni Damajanti; Yeti Rusmiati Hasanah (Research in Chemical Engineering, 2024)
Naphthol dye is one of the synthetic dyes contained in weaving industry waste. One method that can be used to reduce the disadvantageous effects of these substances is by adsorption using activated charcoal adsorbent from coffee grounds. This research aims to determine the character of activated charcoal from coffee grounds and the effect of adsorbent dosage and stirring time on the adsorption of naphthol dye levels. Making activated charcoal from coffee grounds goes through 3 stages, namely the dehydration stage, carbonization stage at 350 oC for 3.5 hours, and activation stage using a 0.1 M HCl activator for 48 hours. The characterization of activated charcoal obtained complies with SNI 06-3730-1995 with results of water content of 3.74%, ash content of 2.12%, and iodine adsorption capacity of 758.29 mg/g, and functional group testing was carried out by varying the adsorbent dosage at 0.125; 0.250; 0.500; 0.750; 1 g (per 100 mL sample) and stirring time for 10; 20; 30; 40; 50 minutes. From the research results, it was obtained the best adsorbent dose and mixing time were 0.5 g and 40 minutes with adsorption efficiency of 98.68% and 99.63%.